Systematic Review of mHealth Interventions for Adolescent and Young Adult HIV Prevention and the Adolescent HIV Continuum of Care in Low to Middle Income Countries - Goldstein, Madeleine; Archary, Moherndran; Adong, Julian; Haberer, Jessica E.; Kuhns, Lisa M.; Kurth, Ann; Ronen, Keshet; Lightfoot, Marguerita; Inwani, Irene; John-Stewart, Grace; Garofalo, Robert; Zanoni, Brian C. (AIDS and Behavior, 2023)
Adolescents and young adults (AYA) in low to middle income countries (LMIC) have poorer outcomes along each step in the HIV continuum of prevention and care compared to younger children or older adults. The use of mHealth technol¬ogy provides a potentially promising implementation strategy for interventions to remedy these disparities. We therefore conducted a systematic review of the English literature and conference proceedings from January 1, 2000 to April 1, 2021 evaluating mHealth interventions targeting AYA along each step of the HIV continuum of care in LMIC. We identified 27 mHealth interventions across the HIV continuum, with no interventions addressing transition from pediatric to adult care. The majority of studies were single arm, uncontrolled or underpowered, with few randomized trials resulting in mixed and inconclusive outcomes. mHealth interventions have potential to remedy disparities along the HIV continuum of care for AYA in LMIC but larger, powered randomized trials are needed
Keywords: Adolescent; HIV; mHealth; low- and middle-income countries; implementation science